Hubungan Penyakit Ginjal Kronik Dengan Stroke - Nouva Afif Fernanda; Tri Wahyuliati (Syntax Idea)
Stroke ranks as the second leading cause of death globally, with an annual mortality rate of approximately 5.5 million. Data from the World Health Organization (WHO) indicates that there are 13.7 million new cases of stroke annually, many of which result in death or permanent disability. Chronic kidney disease is a known risk factor for vascular disorders that can lead to stroke. Decreased kidney function causes endothelial dysfunction, which results in vascular stiffness and elevated systemic blood pressure. If untreated, chronic kidney disease can lead to complications, including stroke. This research is an analytic descriptive observational study with a cross-sectional method. The sample consisted of 60 patients, including 37 ischemic stroke patients and 23 hemorrhagic stroke patients at RS PKU Muhammadiyah Gamping, aged 40-70 years who met the inclusion and exclusion criteria. Data analysis was performed using univariate and bivariate chi-square tests. The study found that 47 out of 60 subjects had chronic kidney disease with stroke. The bivariate test results showed a significant relationship between chronic kidney disease and stroke with a p-value of 0.021 (p < 0.05) and a value of 0.317. There was a correlation between chronic kidney disease and stroke.